Component-oriented information system decomposition - Bagušytė, Lina; Lupeikienė, Audronė (Lietuvos matematikos rinkinys, 2007)
This paper analyses how to bridge the gap between business and supporting information system requirements. It is showed that solution of the problem depends on the analysis methodology of the enterprise system. Decomposition methods used during the analysis stage are discussed. The strategy how to formulate information system functional requirements, taking into account the business system model, is presented. Using the proposed strategy information system is decomposed to interacting components as well.
Keywords: bridging the gap between business and information system; information system decomposition; functional requirements